2020
DOI: 10.3390/cosmetics7030060
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase and Melanogenesis Inhibition by Indigenous African Plants: A Review

Abstract: The indiscriminate use of non-regulated skin lighteners among African populations has raised health concerns due to the negative effects associated with skin lightener toxicity. For this reason, there is a growing interest in the cosmetic development of plants and their metabolites as alternatives to available chemical-derived skin lightening formulations. Approximately 90% of Africa’s population depends on traditional medicine, and the continent’s biodiversity holds plant material with various biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Tyrosinase inhibitors are among the most promising solutions to counter the eventual undesirable effects associated with melanogenesis [ 46 ], with a large demand in the cosmetic and medicinal industry due to their preventive effect on pigmentation disorders and skin-whitening effect [ 47 ]. Indeed, existing evidence [ 48 ] suggests that some phytochemicals present tyrosinase and melanogenesis inhibitor properties. In the present study, either methanolic or ethyl acetate extracts from D. maritima seemed to be effective tyrosinase inhibitors, likely due to the accumulation of phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase inhibitors are among the most promising solutions to counter the eventual undesirable effects associated with melanogenesis [ 46 ], with a large demand in the cosmetic and medicinal industry due to their preventive effect on pigmentation disorders and skin-whitening effect [ 47 ]. Indeed, existing evidence [ 48 ] suggests that some phytochemicals present tyrosinase and melanogenesis inhibitor properties. In the present study, either methanolic or ethyl acetate extracts from D. maritima seemed to be effective tyrosinase inhibitors, likely due to the accumulation of phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Several phytochemicals, including flavonoids, coumarins, tannins, and terpenes, have been reported to possess beneficial effects toward skin, such as antioxidant and anti-inflammatory activities [ 13 , 14 ]. Further research also revealed that these compounds exert skin-whitening activities via inhibition of the TYR and suppression of the melanosome uptake and distribution [ 13 , 14 , 15 , 16 ]. Among them, flavonoids are the one of the most common phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be useful in the modification of biopolymers [ 42 ] and biodegradation [ 21 ]. Most recent reviews on TYRs have focused on TYR inhibitors [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ], which have been intensively studied because the enzyme plays a key role in melanogenesis. TYRs, particularly the readily available TYR from Agaricus bisporus , have often been used as models for testing new inhibitors with potential application in medicine and cosmetics [ 46 , 48 ].…”
Section: Introductionmentioning
confidence: 99%